Effect of needle insertion depth and apical diameter on irrigant extrusion in simulated immature permanent teeth - AKSEL Hacer; ASKERBEYLI Sevinc; CANBAZOGLU Cigdem; SERPER Ahmet (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The aim of this study was to compare the amount of irrigant extrusion in simulated immature permanent teeth when the apical diameter and needle insertion depth were varied. Thirty single-rooted maxillary incisors with straight root canals were selected. The root length was standardized to a length of 9 mm. The teeth were divided into two experimental groups according to the degree of apical enlargement (n = 15). The apices were enlarged to a diameter of 1.10 mm or 1.70 mm by using a #3 or #6 peeso reamer, respectively, to simulate immature teeth. The irrigation solution was applied 2 or 4 mm short of the working length (WL) in each experimental group. The glass vial model was used for the collection of extruded irrigant beyond the root apex. A two-way repeated measures analysis of variance test showed that there was no significant difference between different needle insertion depths (2 and 4 mm short of the WL) in the group with an apical diameter of 1.70 mm (p > 0.05). In the group with an apical diameter of 1.10 mm, a 32% increase in irrigant extrusion was observed when the needle was positioned at 2 mm (p < 0.05). Regarding the effect of apical diameter, the group with a diameter of 1.70 mm showed more apical extrusion of the irrigant (34% increase for the needle positioned at 2 mm and 68% increase for the needle positioned at 4 mm). It was observed that the needle insertion depth and apical diameter have a significant effect on irrigant extrusion in immature permanent teeth.